El boletín de la Institución Libre de Enseñanza BILE - Eulalia Martínez Medrano (Universidad de La Rioja, 2013)
In this article, I show a descriptive analysis about Teaching Free Institution Bulletin in its two periods, such periods are delimited by our Civil War Events. The first period is the most important due to its duration, is extended to sixty years of continued publication from 1877 to the middle of 1936. The second period of this Bulletin, is relatively recent, reappears in 1987 and it is edited by Francisco Giner de los Ríos Foundation. Revising the aim of this magazine, its beginnings, evolution and structure will contribute to the convinction that this Bulletin is considered a very important and imprescindible source for the study of Teaching Free Institution and in the same way, for people who wants to deepen in the evolution of Spanish Education history from the ending of 19th century to the beginning of 20th century. It is specially a necessary source to know our incorporation to New School Pedagogy Movement,educational guidelines, which were followed by Teaching Free Institution and whose principles and realizations had placed the pages of this Bulletin on record.